Komunitas Makrofauna di Kawasan Mangrove Desa Tanjung Leban dan Bukit Batu, Bengkalis - Radith Mahatma; Hairijon Hairijon; Afrimaini Afrimaini (Jurnal Penelitian Sains, 2016)
Information on macrofauna community from mangrove areas in Indonesia is still scarce. The objective of this research were study the abundance and community structure of macrofauna in mangrove area of Tanjung Leban and Bukit Batu Villages, Bengkalis Region, Riau Province. Macrofauna were sampled in September 2014 using corer from 10 plot located in mangrove areas of Tanjung Leban and Bukit Batu Villages. Each plot were sampled three times as a replication. The macrofauna which were collected were classified to Nematoda, Gastropoda, Copepoda, Bivalvia, Polychaeta, Oligochaeta, Tardigrada, Insecta, Holothuroidea, Ostracoda and Syncarida. The average of macrofaunal abundance was 1435 ind./m2 with Nematoda, Gastropoda, and Copepoda as the most dominant taxa. Analysis of ANOVA indicated that the abundance of macrofauna between the plot inside each mangrove area were not statistically different (Tanjung Leban F = 0,96, Bukit batu F = 0,86). Additionally, the Student’s t test indicated that the abundance of macrofauna between mangrove area in Tanjung Leban and Bukit Batu were not statistically different (t = 1,92).